Effect of Community-Based Health Education on Self-Care Behavior Among Adults: A Quasi-Experimental Study - Isymiarni Syarif; Ismarulyusda Binti Ishak (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Self-care behavior is a fundamental component of health promotion and disease prevention among adults. Community-based health education has the potential to enhance self-care practices; however, evidence regarding its effectiveness in real-world community settings remains limited. This study aimed to examine the effect of a community-based health education program on self-care behavior among adults. Methods: A quasi-experimental study with a non-equivalent control group design was conducted involving 60 adult participants. Respondents were allocated into an intervention group (n=30) and a control group (n=30). The intervention group received a structured community-based health education program over four weeks, while the control group received routine health information. Self-care behavior was measured using a structured questionnaire before and after the intervention. Data were analyzed using paired and independent sample t-tests. Results: The intervention group showed a significant improvement in self-care behavior scores after the intervention (p<0.001), whereas no significant change was observed in the control group (p>0.05). The increase in self-care behavior was significantly greater in the intervention group compared to the control group (p<0.001). Conclusion: Community-based health education is effective in improving self-care behavior among adults. Integrating structured educational interventions into community health programs may strengthen primary prevention efforts and promote sustainable healthy behaviors